A novel hepcidin-like in turbot (Scophthalmus maximus L.) highly expressed after pathogen challenge but not after iron overload - Pereiro, Patricia; Figueras Huerta, Antonio; Novoa, Beatriz (Fish & Shellfish Immunology, 2012)
11 páginas, 9 figuras, 1 tabla Hepcidins are antimicrobial peptides with an important role in the host innate immunity. Moreover, it has been reported that mammalian hepcidins present a dual-function being a key regulator in the iron homeostasis. Here, we describe the coding sequence of a novel hepcidin-like peptide in turbot, Scophthalmus maximus. This molecule presents several differences with regard to the previously characterized hepcidin in this flatfish species and it has not the hypothetical iron regulatory sequence Q-S/I-H-L/I-S/A-L in the N-terminal region. Therefore we propose the existence of at least two types of hepcidin in turbot. Moreover, results revealed a higher variability in the mRNA sequences of the novel hepcidin compared with the other form. Constitutive expression of turbot hepcidins (Hepcidin-1 and Hepcidin-2) was analyzed in several tissues and as expected, both molecules were highly represented in liver. On the other hand, the effect of three different stimuli (bacterial or viral infection and iron overloading) in the level of hepcidin mRNA was also examined and a differential response to pathogens and iron was observed. Whereas both hepcidins were affected by pathogen challenge, only Hepcidin-1 was up-regulated after iron overloading. Therefore, this and other evidences suggest that these peptides could be involved in different functions covering the dual role of mammalian hepcidins. Funding from the project CSD2007-00002 “Aquagenomics” of the program Consolider-Ingenio 2010 from the Spanish Ministerio de Ciencia e Innovación. Peer reviewed